2017
DOI: 10.1111/ijfs.13497
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrothermal processing on rutin retention and physicochemical properties of Tartary buckwheat enriched dough and Chinese steamed bread

Abstract: Summary Effects of hydrothermal processing on content changes of rutin, quercetin and total flavonoids and physicochemical properties of Tartary buckwheat (TB) enriched dough and Chinese steamed bread (CSB) were investigated. Rutin loss and bitterness in CSB made from mixed wheat flour and hydrothermally processed TB flour decreased markedly compared with control. Total flavonoids were increased in dough after fermentation but decreased afterwards in CSB significantly (P < 0.05). The development time, stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Therefore, BW is becoming popular for use in a variety of foods, such as breads, noodles, and steamed buns. 10 Polyphenols derived from Australian-grown rice have been demonstrated to inhibit lipid accumulation in adipocytes. 11 Zhang et al 12 found that two anthocyanin-rich extracts from purple and red maize could improve inflammation and insulin resistance in adipocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, BW is becoming popular for use in a variety of foods, such as breads, noodles, and steamed buns. 10 Polyphenols derived from Australian-grown rice have been demonstrated to inhibit lipid accumulation in adipocytes. 11 Zhang et al 12 found that two anthocyanin-rich extracts from purple and red maize could improve inflammation and insulin resistance in adipocytes.…”
Section: Introductionmentioning
confidence: 99%
“…It contains valuable components that protect human health against inflammation and carcinogenesis. , Among its main components, rutin and quercetin are all natural and typical flavonoids with beneficial health effects, such as antitumor and hypotensive activities. , In addition, hydroxybenzoic acid and proanthocyanidins in the bran-aleurone layer of the BW seed have strong peroxyl radical-scavenging activity. Therefore, BW is becoming popular for use in a variety of foods, such as breads, noodles, and steamed buns …”
Section: Introductionmentioning
confidence: 99%
“…This limits its applications in commercial foods, despite its functional benefits [21,22]. 2 of 14 In order to prevent rutin conversion into quercetin, much attention has been given to hydrothermal treatments at 80-121 • C, which lead to the deactivation of rutin 3-glucosidase and thereby maintain high amounts of rutin in TB [16,[23][24][25]. In previous research, three different hydrothermal treatments (steaming, boiling, and autoclaving) were applied to TB grains, and rutin-enriched buckwheat flours were obtained from milling fractions (hull, bran, and flour) [26].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, research into the quality of Mantou has evaluated the use of bran components on the physicochemical and nutritional aspects of Chinese steamed bread (Li et al, ; Liu, Brennan, Serventi, & Brennan, 2017a, 2017b). Flavoring compounds' composition is a crucial factor for consumer's acceptance and the quality (Kim, Huang, Zhu, & Rayas, ; Wang, Fan, & Zhang, ). In recent years, the development of traditional biotechnology for improving Mantou quality has attracted extensive interest.…”
Section: Introductionmentioning
confidence: 99%